2018
DOI: 10.18235/0001331
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Distributional Effects of Energy Taxes and Subsidy Removal in Latin America and the Caribbean

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 6 publications
(7 reference statements)
0
19
0
3
Order By: Relevance
“…International studies on distributional impacts of carbon taxes or energy subsidy removal have shown that consumers are affected in two ways: directly through cost increase of fossil fuels and electricity, and indirectly through increasing production costs affecting prices of all goods and services 14,18,30 . We start by quantifying the impact of carbon pricing on consumers in 16 LAC countries (Table 1) in two basic steps.…”
Section: Direct and Indirect Impacts Of A Carbon Tax On Consumersmentioning
confidence: 99%
See 1 more Smart Citation
“…International studies on distributional impacts of carbon taxes or energy subsidy removal have shown that consumers are affected in two ways: directly through cost increase of fossil fuels and electricity, and indirectly through increasing production costs affecting prices of all goods and services 14,18,30 . We start by quantifying the impact of carbon pricing on consumers in 16 LAC countries (Table 1) in two basic steps.…”
Section: Direct and Indirect Impacts Of A Carbon Tax On Consumersmentioning
confidence: 99%
“…Whether regressive or progressive, carbon taxes adversely impact poor and vulnerable households, undermining social development objectives and potentially reducing support for reforms 15,17,24,[33][34][35][36][37] . The academic literature has established that adequately redistributing carbon revenues can make carbon pricing progressive 15,30,38,39 , and may enhance public support for carbon taxes 15,34,36 .There are two main options to redistribute revenues. One is to reduce other existing taxes, which may come with the additional benefits of improving economic efficiency, especially in countries where the informal sector and tax evasion are substantial issues 15,[40][41][42][43] .…”
Section: Direct and Indirect Impacts Of A Carbon Tax On Consumersmentioning
confidence: 99%
“…However, the risks associated with man-made stranded assets in LAC have been largely overlooked as few studies have attempted to assess their implications for the region or countries therein [10]; there is a clear need for tools and analyses which help decision-makers better understand the potential for stranded assets in LAC and their implications for low-carbon development strategies [35,36]. In addition, financial institutions in LAC are not as robust as in other regions [37,38], which can hamper countries' ability to deal with the instability created by stranded assets.…”
Section: Introductionmentioning
confidence: 99%
“…For Ecuador, the only quantification we are aware of is provided by Feng et al (2018). Using a simple input-output model as part of a regional study on 11 countries, they find that it costs $13 to transfer $1 to bottom-quintile households in Ecuador using gasoline and diesel subsidies; $10 using electricity subsidies, and $7 using LPG subsidies.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing that indirect effects are a crucial driver to consumer costs, we analyze the impact of subsidy removal by applying commodity specific input-output (IO) analysis in combination with household consumption data. Our method gives an upper-bound estimate of the short-term impact of subsidy reform on households, before firms adjust production processes and consumers adapt to new prices, a good indicator for public policy focused on the social acceptability of energy price hikes (Coady et al, 2018;Feng et al, 2018). Compared to Feng et al (2018), we use finer IO data, narrower energy types categories (separating gasoline, diesel, and LPG), and more recent and official estimates of energy subsidies.…”
Section: Introductionmentioning
confidence: 99%